Сладкая женщина: Повести / Ирина Велембовская - Велембовская Ирина Александровна (Ретро, 1994)
Экземпляры: (20180827) / Инвентарный номер: 34281 / Цена: 8.90 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 27 / ББК: 84(2Рос=Рус)6-4